Capacitated Location Allocation Problem of Solar Power Generation in Indonesia using Particle Swarm Optimization - Astungkatara, Arya Wijna; Fath, Hamzah; Putri, Oktaviana; Yana, Anak Agung Istri Anindita Nanda; Normasari, Nur Mayke Eka; Oktavia, Andiny Trie; Rifai, Achmad Pratama (Department Industrial Engineering, University of Muhammadiyah Malang, 2024)
Indonesia has abundant potential for solar energy. The decrease in the cost of solar power generation components can bolster the development of solar power plants. Due to its geographical characteristics, it is essential to analyze the feasibility of using solar power plants as a primary renewable energy source in Indonesia, especially in Sumatra Island. One of the critical aspects of developing solar power plants is determining the suitable location of the power plant and allocating the electricity generated to the regions. Therefore, this study considers the Capacitated Location Allocation Problem (CLAP) to determine the optimal placement of solar power plants on Sumatra Island to minimize investment and transmission costs. To address the problem, we explore three metaheuristics, namely Particle Swarm Optimization (PSO), Simulated Annealing (SA), and Large Neighborhood Search (LNS). The results obtained by these metaheuristic methods show significant differences in cost, with SA providing the best solution with the lowest cost. The investment and transmission cost can be minimized by solving the CLAP to obtain optimal solar power plant placement while enhancing the region's resilience in implementing distributed generation.